2019
DOI: 10.1111/1745-5871.12336
|View full text |Cite
|
Sign up to set email alerts
|

Health geography in New Zealand and Australia: global integration or Antipodean exceptionalism?

Abstract: This paper examines the hallmarks of an emergent and distinctive Australian and New Zealand health geography over the last 30 years. Building on an assessment of the early development of the sub-discipline in the two countries, a review of published work reveals the co-presence of local themes alongside connections to more global perspectives associated notably with health behaviour. Further common themes are the influence of year-round exposure to outdoor spaces and the proximity of "blue spaces" to urban cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 114 publications
0
7
0
Order By: Relevance
“…Second, over a third of the most cited papers are focussed on physical activity and its various health implications. This figure rises further if attention is extended to the wider obesity nexus (Moon and Kearns, 2019) and the presence of terms such as 'obesity', 'walkability', 'diet(ary)' and 'food'. This nexus has been a popular topic more widely amongst submissions to Health & Place for at least the past decade.…”
Section: 'Citation Classicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, over a third of the most cited papers are focussed on physical activity and its various health implications. This figure rises further if attention is extended to the wider obesity nexus (Moon and Kearns, 2019) and the presence of terms such as 'obesity', 'walkability', 'diet(ary)' and 'food'. This nexus has been a popular topic more widely amongst submissions to Health & Place for at least the past decade.…”
Section: 'Citation Classicsmentioning
confidence: 99%
“…The earlier dominance of United Kingdom authors, perhaps reflecting the foundation of the journal in that country, fell away and authors from the United States assumed predominance. Canada and New Zealand retained their authorship shares but Australia doubled its contribution reflecting strong Australian involvement with the growth of research on the obesity nexus (Moon and Kearns, 2019). The remaining tabulated contributor nations point to a strong European contribution and the emergence of China as a research power.…”
Section: The International Dimensionmentioning
confidence: 99%
“…Exceptions were the Netherlands, which largely disappeared by the 1996 meeting but reappeared with the 2015 meeting, and New Zealand. That the New Zealand presence is considerably stronger than that from Australia may have resulted in part from some New Zealand health and medical geographers undertaking postgraduate training in North American or UK universities (Moon & Kearns, ).…”
Section: Conferencing In Health and Medical Geographymentioning
confidence: 99%
“…However, the importance of quality and fit-for-purpose outdoor areas and courtyards for mental health service user health and recovery is not evident in their design. Much research has identified the link between natural light and outdoor spaces as therapeutic and rehabilitative [ 4 , 5 , 6 , 7 , 8 ]. However, although access to outdoor spaces should be established as an imperative for acute mental health facilities, many new wards are still built without direct access to external spaces, even in countries such as the UK or the US [ 2 ].…”
Section: Introductionmentioning
confidence: 99%